Association between characteristic of breakfast menu with energy and macronutrient intake in Cadet of Sekolah Tinggi Penerbangan Indonesia - Siti Hadianti (UHAMKA PRESS, 2018)
Food intake compliance of STPI’s cadet has been provided by the dormitory manager. However, based on observations, there are complaints from the cadets about the taste of food on the breakfast menu that is often tasteless, its appearance looks pale and variations of food that has not been expected. The purpose of this study was to determine the relationship between appearance, taste, and variation of breakfast menu with energy and macronutrient intake of a cadet from Department of Aviation STPI Curug-Tangerang. Research conducted in February to March 2015. Design in this study was cross-sectional with 73 samples taken by simple random sampling. The result of statistical tests, using fisher's exact, showed no relationship between appearance, taste, and variation of breakfast food menu with energy and macronutrient intake.